Application of imidazolinium salts and N-heterocyclic olefins for the synthesis of anionic and neutral tungsten imido alkylidene complexes. Issue 36 (12th April 2016) - Imbrich, Dominik A.; Frey, Wolfgang; Naumann, Stefan; Buchmeiser, Michael R.
Abstract : The convenient synthesis, structural characterization and catalytic properties in olefin metathesis of three anionic tungsten imido alkylidenes and one neutral, NHO-bearing tungsten imido alkylidene complex are presented. Abstract : The synthesis, single crystal X-ray structure and activity in olefin metathesis of novel anionic tungsten imido alkylidene complexes [1, 3-bis-(2, 4, 6-trimethylphenyl)imidazolinium] + [W( N -2, 6-iPr2 C6 H3 )(CHCMe2 Ph)(2, 5-Me2 Pyr)2 Cl] −, [1, 3-bis-(2, 4, 6-trimethylphenyl)imidazolinium] + [W( N -2, 6-iPr2 C6 H3 )(CHCMe2 Ph)(2, 5Me2 Pyr)2 (OC6 F5 )] −, and [1, 3-bis-(2, 6-diisopropylphenyl)imidazolinium] + [W( N -2, 6-iPr2 C6 H3 )(CHCMe2 Ph)(2, 5-Me2 Pyr)Cl2 ] − are reported. Additionally, the first example of a bis(N-heterocyclic olefinium) alkylidene tungstate, W( N -2, 6-iPr2 C6 H3 )(CHCMe2 Ph)(2-methylene-1, 3, 4, 5-tetramethyl-imidazoline)2 (OTf)2, is described, including preparation, crystal structure and catalytic activity.